Violence in Urban Schools in Romania Experimental Results - Cristian, Stan Nicolae (International Journal of Asian Social Science, 2014)
School violence is one of the phenomena not only growing in terms of the frequency with which it manifests itself in urban schools but also one of the factors with a major impact on the educational environment and the physical and psychological sense of security for students. Insecurity, present in the long-term, results in a reduced school performance of students, which makes it necessary to develop and implement programs to eliminate violence in schools. The effectiveness of prevention and combating school violence depends heavily on detailed knowledge of the peculiarities that characterize this phenomenon. In this context, this article focuses on highlighting the defining elements of school violence: What are the most common manifestations, who are the aggressors, where most of these acts of aggression produce and last but not least, what are the reactions of victims of school bullying.